1999
DOI: 10.1016/s0029-7844(99)00236-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral changes during and after lactation

Abstract: A scheduled lactation period of 6 months, followed by a 1-month weaning period, allowed bone mineral density to reach higher values compared with early postpartum, regardless of calcium supplementation and duration of postpartum amenorrhea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
4
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 14 publications
1
92
4
1
Order By: Relevance
“…Since our study was focused on recovery one year postpartum, the impact of pregnancy on bone mass was not determined. In adolescent mothers followed up for a year postpartum, BMC and BMD loss and recovery follow a pattern similar to that observed in adult women (1,2,(20)(21)(22)(23)(24)(25) . To our knowledge, there are no papers reporting that BMC in lactating adolescents ,16 years of age is lower than that of 16-17-year-old adolescents due to the fact that the former may not be completely physiologically mature, as described in teenage pregnancies with respect to linear growth (47) .…”
Section: Discussionsupporting
confidence: 67%
“…Since our study was focused on recovery one year postpartum, the impact of pregnancy on bone mass was not determined. In adolescent mothers followed up for a year postpartum, BMC and BMD loss and recovery follow a pattern similar to that observed in adult women (1,2,(20)(21)(22)(23)(24)(25) . To our knowledge, there are no papers reporting that BMC in lactating adolescents ,16 years of age is lower than that of 16-17-year-old adolescents due to the fact that the former may not be completely physiologically mature, as described in teenage pregnancies with respect to linear growth (47) .…”
Section: Discussionsupporting
confidence: 67%
“…In spite of these low BMD values, fractures were not reported in the study subjects; however, poor bone health may predispose these women to osteoporosis and risk of fracture in later life. Longitudinal studies have reported improvement in spine BMD after weaning as compared to the postpartum period [3,29,30]; although our study design was cross-sectional, we also found higher values of BMD at 3 years compared to that at 1-week postpartum. These results remained unchanged even after adjustment for weight.…”
Section: Discussioncontrasting
confidence: 58%
“…The effect of maternal calcium intake on infant growth remains unclear. Calcium intake during pregnancy may have a positive effect, but the research has provided conflicting results [16][17][18]. A positive relationship between maternal calcium intake and infant length or mid-upper arm circumference has been shown [17,18].…”
Section: Discussionmentioning
confidence: 99%